2010
DOI: 10.7202/044444ar
|View full text |Cite
|
Sign up to set email alerts
|

L’absence de considération pour la notion de genre dans l’intervention auprès des enfants manifestant des comportements sexuels problématiques et auprès de leurs parents

Abstract: À partir d’une recension des écrits portant sur les enfants présentant des comportements sexuels inappropriés à l’endroit d’autres enfants, nous réfléchirons à l’absence de considération pour la notion de genre dans la conceptualisation de cette problématique et par conséquent, dans les programmes d’intervention destinés à cette clientèle. Puisque ces enfants sont majoritairement des garçons, et en nous basant sur la théorie de l’apprentissage social, nous soulignerons le rôle central qu’occupe le père en tant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Interventions in these environments are too often focused on the child’s behavior problems instead of on the reinforcement of their self-regulatory competencies (Chartrand et al, 2013). Studies have shown that caregivers play a significant role in the acquisition of emotion regulation competencies (Morris et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interventions in these environments are too often focused on the child’s behavior problems instead of on the reinforcement of their self-regulatory competencies (Chartrand et al, 2013). Studies have shown that caregivers play a significant role in the acquisition of emotion regulation competencies (Morris et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by allowing the child to exercise judgment, the educator encourages the development of cognitive flexibility. This is especially important for children in residential care who must adapt and respond to difficult situations such as conflicts with educators and peers daily (Chartrand et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation